2019
DOI: 10.1080/15376516.2019.1687629
|View full text |Cite
|
Sign up to set email alerts
|

The role of NF-κB and AhR transcription factors in lead-induced lung toxicity in human lung cancer A549 cells

Abstract: Lead (Pb) is recognized as the first heavy metal of the top six toxic air pollutants threatening human health and the second hazardous substance. Pb exposure is associated with lung impairment and high incidences of lung cancer. Nuclear factor kappa B (NF-jB) and aryl hydrocarbon receptor (AhR) signaling pathways are known to be expressed and play an important role in the lung. However, the link between Pb lung toxicity and NF-jB and/or AhR pathways remains unclear. This study was established to explore the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…Pb-induced mitochondrial dysfunction may also underlie proapoptotic signaling in the exposed lung cells ( Alarifi et al, 2017 ). Activation of NF-κB and aryl hydrocarbon receptor (AhR) pathways has been considered as the potential mechanism underlying Pb-induced inflammation and toxicity in A549 lung cells ( Attafi et al, 2020 ) ( Fig. 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pb-induced mitochondrial dysfunction may also underlie proapoptotic signaling in the exposed lung cells ( Alarifi et al, 2017 ). Activation of NF-κB and aryl hydrocarbon receptor (AhR) pathways has been considered as the potential mechanism underlying Pb-induced inflammation and toxicity in A549 lung cells ( Attafi et al, 2020 ) ( Fig. 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al showed that both omeprazole and 2,3,7,8tetrachlorodibenzo-p-dioxin (TCDD) inhibit the invasion of breast-cancer cells but only omeprazole inhibits the invasion of Panc1 pancreatic cancer cells [27]. Conversely, several studies have shown that AhR activation by endogenous or exogenous ligands leads to increased tumor-cell migration and aggressiveness in breast cancer [28] [29] and lung-cancer cell lines exposed to kynurenine [30] and benzo(a)pyrene (BaP) [31] [32]. Although the impact of AhR expression on carcinogenesis is difficult to characterize, its activation by diverse ligands and the role of various cofactors are important for determining how AhR influences tumor development and phenotype.…”
Section: Ahr Mutations Level Of Expression and Activation In Cancermentioning
confidence: 99%
“…Among which, Cd, Cr, Ni, Cr and As, are considered to be carcinogenic for human with long‐term dusts exposure, and Cr is especially relevant for local children's risk 10 . The toxicity of Pb on lungs has been found to related to the increases in Nuclear factor kappa B (NF‐κB) and aryl hydrocarbon receptor (AHR) levels, which further lead to the increases of nitric oxide synthase (iNOS) and cytochromes of the 1 subfamily (CYP1A1) 11 . Another study shows that Cr(VI) causes alterations in DNA modification and microRNAs 12 .…”
Section: Introductionmentioning
confidence: 99%